Investigating the relationship between competitive intelligence and risk dimensions and job performance of employees in Kerman Saderat bank branches - BARAKCHI, ALI; BEHESHTIFAR, MALIKEH; MOGHADAM, MAHMOOD NEKOIE (The journal of contemporary issues in business and government, 2021)
The aim of this study was to investigate the relationship between competitive intelligence and risk-taking with the employees’ job performance in Kerman Saderat bank branches in 2015. The method of study was descriptive and correlation. The statistical population of this study included all 251 employees of Saderat Bank in Kerman that by using Cochran formula a sample size of 152 people was selected. In this study, three questionnaires of competitive intelligence with 0.91 validity and 0.93 reliability and risk taking questionnaire with 0.93 validity and 0.95 reliability and job performance questionnaire with 0.92 validity and 0.84 reliability were used. The collected data were analyzed by using Smart PLS 2. The results showed that there is a relationship between competitive intelligence and risk-taking and the job performance among the employees working in Kerman Saderat bank branches. Among the components of competitive intelligence; a direct and significant relationship was found between technical knowledge and strategic and social knowledge with job performance of the employees. Among the risk taking components; the two components of credit risk, operational risk, and market risk were significantly correlated with job performance of the employees. Therefore, it is recommended that the bank managers have a correct and scientific management of the bank assets and debts and they assess their own current and potential competitors to take step toward a better performance of the employees in order to have growth and profitability in the banks and attract financial resources.